(untitled) (SUNGKAI: Jurnal Aqidah dan Filsafat Islam, 2023)
This research is motivated by various cases of modern human spirituality which are influenced by the West, thus leading to various crises in modern human spirituality. The aim of this research is to find the problems that arise, such as: the emergence of secularism is a form of problem that causes damage to the spirituality of modern humans which is separated from the understanding of religion which teaches about developing the spirituality of modern humans, while fundamentalism is a form of crisis because this movement teaches violence which has an impact on spirituality. Modern humans carry the name of religion, of course fundamentalism is a form of deviation from religion which can cause problems in filling the spiritual void of modern humans. This approach is qualitative in nature, this approach was chosen because it is compatible with the nature of the research, which the researcher collected based on data obtained from book essays related to Seyyed Hossen Nasr’s views on the views of Sufism in filling the spiritual void of modern humans. Researchers used descriptive, inductive data collection techniques and library research. The results found by the author are that in Seyyed Hossen Nasr’s vision in filling the void of modern human spirituality and building human awareness, he uses the understanding taught by religion as the basis of teachings that give confirmation to humans to return to the sanctity of Insan Kamil because in themselves humans are bound by its properties.